Pendampingan Mahasantri melalui Diskusi Interaktif untuk Meningkatkan “High Order Thinking Skills” di PP. Sunan Drajat - Ahmad Zidan Danutirto; Muhammad Prasetyo Nugroho; M. Nur Qomaruddin A.; Abdul Hamid; Rachmad Ardy Kurniawan; M. Muhlis (Santri: Journal of Student Engagement, 2022)
Assistance for students of the Sunan Drajat Islamic Boarding School in order to prepare cadres who have the ability or skill "High Order Thinking" in order to improve students' thinking abilities. The mentoring that was carried out within a month had inspired the students at the Sunan Drajat Islamic Boarding School, Banjarwati, Paciran Lamongan. The assistance carried out through interactive discussions is not just an ordinary discussion but also with the latest methods and innovations in order to process the thoughts of the students of the Sunan Drajat Islamic Boarding School for the formation of critical characters but still understand the rules and do not impose their own will and thoughts. This mentoring also aims to equip the students of the Sunan Drajat Islamic Boarding School in the ability both in terms of knowledge, thinking and skills that students have. And the results later on what has been achieved in this mentoring activity have met the standard both in critical thinking skills and soft skills, namely high older thinking skills, basic skills that must be mastered by students at the Sunan Drajat Islamic Boarding School.